Computational and spectroscopy study of melatonin - Omar, Rebaz; Koparir, Pelin; Ahmed, Lana; Koparir, Metin (Natl Inst Science Communication & Information Resources-Niscair, 2021)
Hartree-Fock (HF) and Density Functional Theory (DFT) play an important role in computational quantum theory especially in physical chemistry. Melatonin is a hormone produced naturally by the pineal gland that prevents the production of melanin. It is believed to be involved in regulating the reproductive cycle. The energy bandgaps for melatonin structure have been calculated using DFT and HF method at different basis sets. The bond length, bond angle, and dihedral angles for the melatonin compound have been described. The atomic orbital (GIAO), H-1 and C-13 NMR chemical shifts of the title compound in the ground state have been calculated using the density functional method (B3LYP) with the 6-31G(d,p) basis set. Using the PCM model, the electronic absorption spectra have been determined using the TD-DFT method based on the B3LYP/6-311G(d,p) level optimized structure in different solvents (DMSO, ethanol, aniline, chloroform, THF, and diethyl ether), the maximum wavelength has been observed in DMSO solvent. Frontier molecular orbitals (FMOs), Molecular electrostatic potential (MEP) surfaces, and thermodynamic parameters have been described for melatonin molecule.
Keywords: Melatonin; Density Functional Theory (DFT); Hartree-Fock (HF); UV-Vis; ESP; thermodynamic